Analisis Strategi Soar Pt. Xyz Dalam Meningkatkan Penjualan Bahan Baku Kimia Untuk Industri Tekstil, Kayu, Pakaian Dan Deterjen - Calvin Chiu (Universitas Tarumanagara, 2019)
PT. XYZ is a private multinational company engaged in chemical type commodities trading with sodium sulphate, sodium carbonate and hydrogen peroxide – three of the most common chemicals used in textile, pulp & paper and detergent industry – as their main traded commodities. However, due to many opportunities available and the company’s experience as an international trader, marketing plan should not be ignored especially when the company is still relatively new as a supplier. Based on last year sales revenue alone, PT. XYZ placed third among four other companies, placing PT. XYZ as a market follower and thus needed to formulate an offensive strategy to achieve higher sales. The method used in this study is by using SOAR tool instead of SWOT analysis and translated into Treacy and Wiersema’s value disciplines. consisted of three strategies, i.e. operational excellence, customer intimacy and product leadership. The study found that there is a need for the company to use a combined strategy of operational excellence and customer intimacy.